Coping with salinity stress: segmental group 7 chromosome introgressions from halophytic Thinopyrum species greatly enhance tolerance of recipient durum wheat - Tounsi, Sana; Giorgi, Debora; Kuzmanović, Ljiljana; Jrad, Olfa; Farina, Anna; Capoccioni, Alessandra; Ben Ayed, Rayda; Brini, Faiçal; Ceoloni, Carla (Frontiers in Plant Science, 2024)
Increased soil salinization, tightly related to global warming and drought and exacerbated by intensified irrigation supply, implies highly detrimental effects on staple food crops such as wheat. The situation is particularly alarming for durum wheat (DW), better adapted to arid/semi-arid environments yet more sensitive to salt stress than bread wheat (BW). To enhance DW salinity tolerance, we resorted to chromosomally engineered materials with introgressions from allied halophytic Thinopyrum species. “Primary” recombinant lines (RLs), having portions of their 7AL arms distally replaced by 7el1L Th. ponticum segments, and “secondary” RLs, harboring Th. elongatum 7EL insertions “nested” into 7el1L segments, in addition to near-isogenic lines lacking any alien segment (CLs), cv. Om Rabia (OR) as salt tolerant control, and BW introgression lines with either most of 7el1 or the complete 7E chromosome substitution as additional CLs, were subjected to moderate (100 mM) and intense (200 mM) salt (NaCl) stress at early growth stages. The applied stress altered cell cycle progression, determining a general increase of cells in G1 and a reduction in S phase. Assessment of morpho-physiological and biochemical traits overall showed that the presence of Thinopyrum spp. segments was associated with considerably increased salinity tolerance versus its absence. For relative water content, Na+ accumulation and K+ retention in roots and leaves, oxidative stress indicators (malondialdehyde and hydrogen peroxide) and antioxidant enzyme activities, the observed differences between stressed and unstressed RLs versus CLs was of similar magnitude in “primary” and “secondary” types, suggesting that tolerance factors might reside in defined 7el1L shared portion(s). Nonetheless, the incremental contribution of 7EL segments emerged in various instances, greatly mitigating the effects of salt stress on root and leaf growth and on the quantity of photosynthetic pigments, boosting accumulation of compatible solutes and minimizing the decrease of a powerful antioxidant like ascorbate. The seemingly synergistic effect of 7el1L + 7EL segments/genes made “secondary” RLs able to often exceed cv. OR and equal or better perform than BW lines. Thus, transfer of a suite of genes from halophytic germplasm by use of fine chromosome engineering strategies may well be the way forward to enhance salinity tolerance of glycophytes, even the sensitive DW.